2017
DOI: 10.1111/jsr.12636
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and its relation to cognition and behaviour in preschool‐aged children of the general population: a systematic review

Abstract: This is the first systematic review of the literature on sleep and its relation to cognition and behaviour in preschool-aged children. In comparison with the literature focused on school-aged children, knowledge involving preschoolers is rather sparse. A total of 26 studies was included in this review, which revealed a high degree of heterogeneity regarding the type and means of measuring sleep variables and behavioural and cognitive variables, as well as the statistical methods employed. Amongst the 13 articl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
90
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 60 publications
6
90
2
4
Order By: Relevance
“…For young TD children, longer nighttime sleep duration is associated with better early language development [3,22], although the effect size usually is small. The relation between nighttime sleep duration and cognitive development is less clear [1,23]. Less nighttime sleep is associated with difficulties in emotion regulation [23], and both reduced nighttime sleep duration [22,24] and excessive daytime sleepiness [25] have been associated with externalizing problems.…”
Section: Association Of Child Sleep Characteristics and Problems To Lmentioning
confidence: 99%
See 2 more Smart Citations
“…For young TD children, longer nighttime sleep duration is associated with better early language development [3,22], although the effect size usually is small. The relation between nighttime sleep duration and cognitive development is less clear [1,23]. Less nighttime sleep is associated with difficulties in emotion regulation [23], and both reduced nighttime sleep duration [22,24] and excessive daytime sleepiness [25] have been associated with externalizing problems.…”
Section: Association Of Child Sleep Characteristics and Problems To Lmentioning
confidence: 99%
“…Child sleep problems impact daytime behavior [1], physical health, parental stress, and quality of life for typically developing (TD) children and their families [2]. Negative outcomes of sleep problems include language delay [1,3], cognitive delay [4], and behavior problems [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, longitudinal studies suggested that these troubles may persist later in childhood, and even during adolescence and adulthood (Al Mamun et al., ; Byars, Yolton, Rausch, Lanphear, & Beebe, ; Morgenthaler et al., ; Quach, Hiscock, Canterford, & Wake, ). Additionally, previous studies showed that insufficient quality and quantity of sleep in children and adolescents are associated with several negative mid‐ and long‐term consequences (Chaput et al., ; Dewald, Meijer, Oort, Kerkhof, & Bögels, ; Fatima, Doi, & Mamun, ; O'Callaghan et al., ; Reynaud, Vecchierini, Heude, Charles, & Plancoulaine, ), including behavioural and cognitive performance (Dewald et al., ; Reynaud et al., ), or increased risk of overweight and obesity (Fatima et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…2009). Additionally, previous studies showed that insufficient quality and quantity of sleep in children and adolescents are associated with several negative mid-and long-term consequences (Chaput et al, 2016;Dewald, Meijer, Oort, Kerkhof, & Bögels, 2010;Fatima, Doi, & Mamun, 2015;O'Callaghan et al, 2010;Reynaud, Vecchierini, Heude, Charles, & Plancoulaine, 2018), including behavioural and cognitive performance (Dewald et al, 2010;Reynaud et al, 2018), or increased risk of overweight and obesity (Fatima et al, 2015).…”
mentioning
confidence: 99%